Brief Analysis of Approaches to Peak Regulation for Natural Gas Storage - Shang, Ben; Chen, Yunfeng; Zhang, Dong (International Journal of Electric Power and Energy Studies, 2024)
With the increasing proportion of natural gas in energy supply, considering the changes in urban natural gas consumption time and peak pipeline pressure, how to balance gas supply and consumption will become the key to ensuring winter supply. This article aims to study and solve the problem of natural gas storage peak shaving, analyze the current situation and the advantages and disadvantages of different situations, and propose specific solutions. By studying underground gas storage facilities, liquefied natural gas (LNG) storage, compressed natural gas (CNG) storage, distributed gas storage systems, intelligent scheduling, and policy market mechanisms, new ideas are provided for building a low-carbon, efficient, and flexible gas storage peak shaving system.